2018
DOI: 10.3390/toxins10040148
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deoxynivalenol and Zearalenone on the Pig Large Intestine. A Light and Electron Microscopy Study

Abstract: The contamination of feed with mycotoxins results in reduced growth, feed refusal, immunosuppression, and health problems. Deoxynivalenol (DON) and zearalenone (ZEN) are among the most important mycotoxins. The aim of the study was to examine the effects of low doses of these mycotoxins on the histological structure and ultrastructure of the large intestine in the pig. The study was performed on 36 immature gilts of mixed breed (White Polish Big × Polish White Earhanging), which were divided into four groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…ZEN increase ER-alpha, activate Wnt/β-catenin signaling and repress TGF-β in the small intestine of castrated male pigs, inducing a pro-proliferative/pre-cancerous phenotype, characterized by over-expression of MCM3 and VIM. This suggests that ZEN disturbs the ISC microenvironment, promoting a pro-cancerous, proliferative state in the intestine that has been already described in the literature [12,[28][29][30]59]. Our results also show that ZEN can modulate the energy sensing-related phenotype of intestinal tissues without inducing inflammation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…ZEN increase ER-alpha, activate Wnt/β-catenin signaling and repress TGF-β in the small intestine of castrated male pigs, inducing a pro-proliferative/pre-cancerous phenotype, characterized by over-expression of MCM3 and VIM. This suggests that ZEN disturbs the ISC microenvironment, promoting a pro-cancerous, proliferative state in the intestine that has been already described in the literature [12,[28][29][30]59]. Our results also show that ZEN can modulate the energy sensing-related phenotype of intestinal tissues without inducing inflammation.…”
Section: Discussionsupporting
confidence: 84%
“…The main reason for ZEN sensitivity is that pigs, similar to humans, convert ZEN into the more estrogenically active α-zearalenol [27]. In vivo, whereas some authors found no morphologic changes [28,29], others found that chronic exposure of pigs to ZEN led to transient morphological modifications in the small intestine during the first weeks of exposure [29], or to an increase in the number of Paneth cells at the bottom of the intestinal crypts [28]. At the cellular and molecular level, several reports have described changes in the gene expression of pro-inflammatory cytokines, genes implicated in the induction of a proliferative state such as Dickkopf-related protein 1 (DKK1), β-catenin or the proto-oncogene c-Myc [8,12,30].…”
mentioning
confidence: 99%
“…Since mycotoxins are present in food and drinking water, the gastrointestinal (GI) tract is the part of the body that first comes into contact with these toxic factors [ 8 ]. A relatively large number of studies have described mycotoxin-induced morphological and functional changes in the GI tract, whose character depends on the type of mycotoxin, mammal species studied, as well as the degree and length of exposure to mycotoxins [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The most common effects of mycotoxins on the GI tract include inflammatory and necrotic changes, disturbances in secretory activity and metabolism of the enterocytes, damage to the intestinal barrier and dysfunction in intestinal absorption [ 10 , 11 , 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…De Ruyck et al [ 27 ] observed that various substances, including carcinogenic compounds, are accumulated in the bodily tissues of animals exposed to ZEN. The epithelium of the digestive tract is exposed first to the ingested low doses of ZEN [ 28 , 29 , 30 , 31 ]. The intestinal mucosa prevents antigens, including undesirable substances such as ZEN, commensal bacteria, and pathogens from penetrating deeper tissues [ 32 ].…”
Section: Introductionmentioning
confidence: 99%